Time to blood culture positivity: An independent predictor of infective endocarditis and mortality in patients with Staphylococcus aureus bacteraemia. (April 2019) - ; Chirouze, Catherine; Curlier, Elodie; Descottes-Genon, Cécile; Hoen, Bruno; Patry, Isabelle; Vettoretti, Lucie; Chavanet, Pascal; Eicher, Jean-Christophe; Gohier-Treuvelot, Sandrine; Greusard, Marie-Christine; Neuwirth, Catherine; et al.
Abstract: Objectives: Time to blood culture positivity (TTP), a routinely available parameter in automated blood culture systems, may be a proxy for infectious burden in patients with bloodstream infections. We aimed to study the association between TTP and infective endocarditis (IE), or death, in patients with Staphylococcus aureus bacteraemia. Methods: VIRSTA is a multicentre prospective cohort study that included all adult patients with S. aureus bacteraemia in eight university hospitals in France (2009–2011). We analysed data from four centres which collected data on TTP. Regression models were used to study the association between TTP and definite IE (Duke-Li criteria), and 30 day-mortality. Results: We included 587 patients with S. aureus bacteraemia: mean age was 65.3 ± 16.3 years, 420 out of 587 patients (71.6%) were male, 121 out of 587 (20.6%) died, and 42 out of 587 (7.2%) had definite IE. Median TTP of first positive blood culture was 13.7 h (interquartile range 9.9–18). On multivariate analysis, 30-day mortality was associated with TTP ≤13.7 h (74/295 (25.1%) vs. 47/292 (16.1%), p 0.02), as well as old age, McCabe score, methicillin resistance, stroke, pneumonia, and C-reactive protein. TTP was also independently associated with IE, but with a U-shape curve: IE was more common in the first (TTP <10 h, 17/148, 11.5%), and the last (TTP ≥18 h, 8/146, 5.5%) quartiles of TTP, p 0.002. Conclusions: TTP provides reliable information in patients with S. aureus bacteraemia, on the risk of IE, and prognosis, with short TTP being an independent predictor of death. These data, readily available at no cost, may be used to identify patients who require specific attention.